Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content: 1. Ecotourism for the Sustainability of Protected Areas Soqotra Island: Case Study – Yemen Dr. Bardees Taher Alokab 2. Territorial Information System and the Enhancement of Territorial Governance Mechanisms in the Countryside of Taourirt Province (Eastern Region – Morocco) Dr. JAOUAD EL BAZOUI, Dr. Mohammed LAKHDARI, Dr. Mohamed AZIACH 3. Solidarity And Social Economy and the Question of Territorial Governance: The Case of the Almond Chain Development Program in the Province of Taourirt- East Region (Morocco) Dr. Mohammed LAKHDARI, Dr. Mohamed AZIACH, Dr. Jaouad El-BAZOUI 4. Women driving a car and its role in achieving self-independence and raising the level of quality of life among a sample of working women in the city of Jeddah Ms. Najwa Abdullah Al-Gamdi, Dr. Suha Omar Alharthi 5. Arab-Zionist Struggle Terminology of Place Naming Dr. Amal Mahmoud Abu Own, Prof. Ihsan Yacoub Al-Deek 6. The natural components of mountain Shada and their role in achieving sustainable tourism Ms. Zahra Ahmed Alzahrani